Immune Evasion Strategies of Relapsing Fever Spirochetes - Röttgerding, Florian; Kraiczy, Peter (Frontiers in Immunology, 2020)
Relapsing fever (RF) is claimed a neglected arthropod-borne disease caused by a number of diverse human pathogenic Borrelia (B.) species. These RF borreliae are separated into the groups of tick-transmitted species including B. duttonii, B. hermsii, B. parkeri, B. turicatae, B. hispanica, B. persica, B. caucasia, and B. myiamotoi, and the louse-borne Borrelia species B. recurrentis. As typical blood-borne pathogens achieving high cell concentrations in human blood, RF borreliae (RFB) must outwit innate immunity, in particular complement as the first line of defense. One prominent strategy developed by RFB to evade innate immunity involves inactivation of complement by recruiting distinct complement regulatory proteins, e.g. C1 esterase inhibitor (C1-INH), C4b-binding protein (C4BP), factor H (FH), FH-like protein-1 (FHL-1), and factor H-related proteins FHR-1 and FHR-2, or binding of individual complement components and plasminogen, respectively. A number of multi-functional, complement and plasminogen-binding molecules from distinct Borrelia species have previously been identified and characterized, exhibiting considerable heterogeneity in their sequences, structures, gene localization, and their capacity to bind host-derived proteins. In addition, RFB possess a unique system of antigenic variation, allowing them to change the composition of surface-exposed variable major proteins, thus evading the eacquired immune response of the human host. This review focuses on the current knowledge of the immune evasion strategies by RFB and highlights the role of complement-interfering and infection-associated molecules for the pathogenesis of RFB.